AN ANALYSIS OF ENGLISH TEXTBOOK ENTITLED “STOP BULLYING NOW” PUBLISHED BY KEMENDIKBUD RI - Indah Fitriyani; Fitri Aprianti; Ikariya Sugesti (National Conference on Language, Education, and Technology Proceeding, 2021)
The study examined the English text book “Stop Bullying Now” Published By Kemendikbud RI based on the Cunningsworth criteria. The study found out the quality of the English textbook “Stop Bullying Now” for class XI. The method employed in this study is qualitative descriptive. The study focuses the textbooks to fit the criteria based on Cunningsworth theory. In data-mining researcher using documentary analysis. Researcher analyzed 3 chapters of the 5 chapters of the textbook Published By Curriculum and Book Center, Balitbang, Kemendikbud. Studies show that the textbooks “Stop Bullying Now” are as good as the Cunningsworth criteria. It meets the criteria of the Cunningsworth and includes a good English textbook because it contains language content, skills, and topics. The study examined the English text book “Stop Bullying Now” Published By Kemendikbud RI based on the Cunningsworth criteria. The study found out the quality of the English textbook “Stop Bullying Now” for class XI. This study can be used by teachers as a guide in teaching so that teachers can use this textbook for school teaching activities. This study can be used by teachers as a guide in teaching so that teachers can use this textbook for school teaching activities.